Smooth operating and other social acts. - ROLAND LEANDER WILLIAMS (STATE UNIV OF NEW YORK PR, 2022)
Through a cultural study of writings about slavery in the United States, Smooth Operating and Other Social Acts uncovers a mode of behavior adopted by African Americans for relief from the brutality of black bondage. Roland Leander Williams grants that African Americans have been beaten, but he guarantees that they have not been broken. While he acknowledges that they have been demeaned, he assures that they have not been diminished. Williams confesses that African Americans have been done harm, but he confirms that they have not become disheartened. Close readings of classic slave narratives, along with some neo-slave narratives--including The Conjure Woman (1899), Kindred (1979), Dessa Rose (1986), and The Good Lord Bird (2013)--furnish proof that African Americans have preserved their dignity and elevated their status through ingenious applications of improvisation. Smooth Operating and Other Social Acts establishes as well that a dim view of African Americans, propagated by black bondage, bears a resemblance to sexual discrimination, which prompts female targets of its gaze to practice dissembling.